COASTLINE MAPPING IN KOTO TANGAH DISTRICT USING MULTITEMPORAL REMOTE SENSING IMAGES, 2002, 2012 AND 2022 - Rizka Nofriyanti; Febriandi Febriandi (Remote Sensing Technology Study Program, 2022)
The purpose of this study was to determine changes in the coastline and the extent of abrasion and accretion that occurred from 2002 to 2012 and 2012 to 2022. This study utilized geographic information systems and remote sensing techniques in the form of Landsat 7 imagery in 2002, 2012 and Landsat 8 imagery. in 2022. The research uses the Digital Shoreline Analysis System method 'DSAS' which Net Shoreline Movement (NSM) and Endpoint Rate (EPR). To calculate the area of ​​abrasion and accretion use the Calculate Geometry menu. The results of this study are maps of shoreline changes from 2002 to 2012 and from 2012 to 2022. From 2002 to 2012 the rates and distances that occur are accretions 2012 to 2022, the change in the coastline, the rate and distance that will occur is abrasion. The coastline area due to abrasion increased by 57,702 m in 2002-2012 and 2012-2022, while the coastline area due to accretion in 2002-2012 and 2012-2022 decreased by 61,851 m.